PENINGKATAN PRODUKSI TANAMAN OKRA AKIBAT PEMBERIAN BEBERAPA JENIS MIKORIZA DAN DOSIS ROCK PHOSPHAT PADA TANAH SALIN - Mizan Maulana; Darmadi Erwin Harahap (Journal Agro-Livestock, 2023)
Okra (Abelmochus esculentus L. Moench) has a fairly high nutritional content where every 100 grams of young okra fruit contains 33 calories, 7 grams of carbohydrates, 3.2 grams of fiber and 81 milligrams of calcium. Okra fruit contains a lot of mucilage due to its high fiber content. This study aims to determine the effect of rock phosphate dose and types of mycorrhizae and the interaction between these two factors on the growth and yield of okra in saline soil. The results of the research conducted showed that the dose of mycorrhiza had a very significant effect on the growth and yield of okra plants. The best dose of mycorrhiza was 10 g/plant for the best type was Acauluspora. This shows that a dose of 10 g/plant with the Acauluspora type on okra yields on ultiisol soil has given the best results both in the vegetative phase which can be seen in plant height parameters 15 and 30 HST. The dose of rock phosphate is 200 g which can be seen in the 300 g planting parameter which can be seen in almost all the observed variables. Hyphae in the soil can spread widely which helps absorb more water. The best yields of okra plants were found in the administration of mycorrhizal dose of 10 g/planting on fruit weight variables of plants mycorrhizal colonization on vase vegetative roots and mycorrhizal colonization on plant roots in the generative phase.